WHY WORK? A CULTURALLY INFORMED CRITIQUE OF PAST AND PRESENT SHOP FLOOR INTERPRETATIONS OF WORK - MIHAELA KELEMEN; DIRK BUNZEL; PAUL WILLIS (Annals of the University of Petrosani: Economics)
This paper provides a cultural critique of the meanings of work as theytranscend different modes of production. Twenty years on from the collapse of state socialism,Western experts are still called upon to prescribe ‘the best way’ for how productive workshould be conducted/managed across the non-Western world (Jankowicz, 1993; 1994; Kostera,1995, Kelemen, 1999). This ‘one best way’ usually assumes that the basic unit of analysis is therational, utility-maximising individual; a species, bred inside Westernized secondary andtertiary educational institutions, business schools, or (vocational) training courses, all of theseproducing their special form of ‘learning to labour’ (Willis, 1977). Thus equipped, this species– what we might call, for the time being, the ‘model-worker’ - is bound to inhabit a ratherinhabitable place, an arena of in increasingly global capitalism: the market.